IMPLIKASI BADAN PERTANAHAN NASIONAL TERHADAP PEMBATALAN SERTIPIKAT HAK PAKAI BERDASARKAN PUTUSAN PENGADILAN (STUDI KASUS PUTUSAN PENGADILAN NEGERI JAKARTA UTARA NO.612/PDT.G/2019/PN.JKT.UTR) - Siti Aliyah (2023)
The case for canceling the certificate was based on Court Decision Number: 612/Pdt.G/2019/PN.Jkt.Utr, that the legal owner of a plot of land and buildings on it was named Lusi Siregar (plaintiff) with proof of a sale and purchase agreement obtained from Alm. Nurjaman and Nasuha (the seller) on December 30, 2000. In 2005, on the advice of the mother and sister of the Plaintiff, the house was to be lived by his older brother, Rudy (the defendant), because at that time the defendant was still renting the house. Unbeknownst to the plaintiff, the name of the house has been changed to the name of the Defendant where a usufructuary certificate has been recorded at the North Jakarta Administrative City Land Office on the basis of a purchase from Mr. Nurzaman and Mrs. Nasuha signed by Nurzaman and Mrs. Nasuha's thumbprint as well as the signatures of Lusi Siregar and Rudy dated September 7 2005, which the Plaintiff and the seller never felt had signed the sale and purchase agreement. The formulation of the problem in this research is what are the implications and responsibilities of the National Land Agency (BPN) for issuing usufructuary certificates based on falsification of sale and purchase deed; how is the legal certainty of a right of use certificate that was canceled based on a Court Decision. The method used in this research is normative juridical research. The results of his research showed that Rudy had committed an unlawful act because the making of a usufructuary certificate was based on a vague or unclear basis that contradicted the applicable laws and regulations, so that BPN was responsible for implementing the Court's Decision regarding the Cancellation of the Certificate. Implications of the National Land Agency for the Issuance of Land Use Rights based on a fake sale and purchase deed which is not valid according to law due to administrative defects and a usufructuary certificate owned by the Defendant based on decision number NO. 612/PDT.G/2019/PN.JKT.UTR is declared invalid or has no legal force so that legal certainty from a usufructuary certificate that is canceled based on a Court decision is by making an application for the cancellation of the certificate to the BPN that issued the certificate, so that by the cancellation of the usufructuary certificate makes the evidence of ownership of the land rights the same as it was before the existence of the certificate which did not harm the actual land owner.